The Survival of Identity of Cherokee People in 20th Century as Depicted in Patricia Riley’s Damping Down the Road and Wisteria - Ovi Harum Wulan (Universitas Gadjah Mada, 2017)
The lives of the Cherokee family in the 20th Century in Patricia Riley’s Damping Down the Road and Wisteriagive a description in how the characters in the family have different viewpoint on seeing Native American, Cherokee. The research is to find out the ways used by the Cherokee people to survive in the whites’ culture society and to find the reasons for the Cherokee people survive in such way. The research is conducted under American Studies discipline, by applying postnational paradigm. Moreover, mimicry, decolonization theory proposed by Frantz Fanon, to analyze the ways used by the characters to survive in the whites’ culture society and drive theory proposed by Clark L. Hull to answer the reason for the natives to survive in such ways.The research finds that both short stories are depicted to do mimicry and to keep their Cherokee culture. The characters who do mimicry are those who want to be accepted in the whites’ culture society meanwhile the characters who keep their Cherokee culture are those who have mission in maintaining the Cherokee culture for the next generation. By doing mimicry and keeping the traditional culture, they could survive in the whites’ culture society in order to show their existence. Keywords: Cherokee, whites’ culture, mimicry, decolonization, and drive theory